PUBLIC SPACES AND GENDER: TESTING THE RELATIONSHIP OF SPATIAL CONFIGURATION OF STREET NETWORKS - Khalid, Nurul Shakila; Raja Othman, Raja Norashekin; Marzukhi, Marlyana Azyyati (PLANNING MALAYSIA, 2020)
The purpose of this paper is to examine the spatial dominance in public spaces from a gendered and women perspectives and to analyse the relationship with the spatial configuration of street networks. In analysing the street networks in Space Syntax, the question arises; to what extent the movement and activity may explain street integration among gender-based pedestrians. The result found that there is a correlation between spatial configurative analyses and women present in the streets. In essence, the less integrated streets attract more women pedestrians and improve better quality of space. The research is relevant to spatial design interventions and policymaking to enhance gender equal access to public space.